(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article covers the theoretical and practical foundations of the formation of professional and psychological competencies in students in the process of teaching technology. The role of psychological preparation, professional motivation, innovative activity-oriented training and a competency-based approach in the professional formation of a person is scientifically analyzed. The role of technology in preparing students for the labor process, the role of teacher activity in the process of psychological stability of students and professional self-awareness are revealed. The article also substantiates methods for increasing the psychological readiness of students through the use of digital and innovative technologies in education.